2017
DOI: 10.1016/j.anorl.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy and vocal fold scarring

Abstract: Vocal fold microstructure is complex and can be affected by laryngeal microsurgery, inducing scarring that prevents mechanical uncoupling of epithelium and muscle, leading to vibration disorder and disabling dysphonia. Treatment options presently are few, and often without efficacy for vibration, having only an impact on volume to reduce glottal closure defect. The present review of the literature had two aims: (i) to report the current state of the literature on cell therapy in vocal fold scarring; and (ii) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 41 publications
1
42
0
2
Order By: Relevance
“…1,28,29 Cell-based therapy includes transplantation of pluripotent stem cells, mesenchymal stromal cells, or mature fibroblasts. Recent literature reviews [30][31][32] identified more than 30 in vitro and in vivo studies on cell therapy for vocal fold scarring alone. Translating these promising concepts to human trials has been much slower, as significant assurances of feasibility and safety are prerequisites before human administration.…”
Section: Discussionmentioning
confidence: 99%
“…1,28,29 Cell-based therapy includes transplantation of pluripotent stem cells, mesenchymal stromal cells, or mature fibroblasts. Recent literature reviews [30][31][32] identified more than 30 in vitro and in vivo studies on cell therapy for vocal fold scarring alone. Translating these promising concepts to human trials has been much slower, as significant assurances of feasibility and safety are prerequisites before human administration.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis is a histological finding often seen in scar tissue and in our model the follow up time was too short to analyze the possible impact on scar tissue formation. There is evidence that cell therapy might be able to prevent vocal fold scaring in laryngeal microsurgery and fibrous keloid formation after skin incision in acute trauma model [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…The other uses cells to directly restore normal anatomy. Many cell types have been studied for vocal fold regeneration,46 but fibroblasts and stem cells seem to be the most promising to date.…”
Section: Regenerative Medicine Advances In Oto-hnsmentioning
confidence: 99%